Find f'(x) and f''(x) when f(x) = 3x^2 +7x - 3

We know that when f(x) = x^n, f'(x) = nx^n-1       (1)

So we apply this to all components of f(x), giving 

f'(x) = 2(3x) + 7 = 6x +7

to find f''(x), we apply (1) to f'(x). Giving

f''(x) = 6                                                                 

 

Answered by Georgiana P. Maths tutor

5208 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the derivative of f(x) = 2xe^x


Expand and simplify (n + 2)^3 − n^3.


Integrate cos(x)sin^2(x)


A function is defined parametrically as x = 4 sin(3t), y = 2 cos(3t). Find and simplify d^2 y/dx^2 in terms of t and y.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences